Experience from MAP-T Testing - Cordeiro, Edwin; Carnier, Rodrigo; Moreiras, Antonio (Anais do Workshop Pré-IETF (WPIETF), 2014)
This document describes the testing result of a network using MAP-T dual translation solution, by providing an overview of user applications' behavior with a shared IPv4 address. The MAP-T software was developed by CERNET Center and the test environment was on NIC.br network with real and virtualized machines.